Taboo Words in Main Characters of Death Proof Movie - Oldi Simon; Syarifuddin Ahmad; Rahman Taufiqrianto Dako (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
The use of taboo words is strongly influenced by culture. In the growing discourse of use of taboo words in social reality, men are often portrayed to have discourteous traits and utter any form of taboo words when compared to women. However, a movie entitled Death Proof does not show the same trend. The present research aimed at investigating taboo words in the mentioned movie by focusing on their types and motives. Through the utilization of observation and documentation techniques, the data comprised utterances of the main characters that contained taboo words. The results revealed that the main characters employed taboos of profanity, obscenity, vulgarity, epithet and insult. Pertaining to women, they also fulfill those various classifications. Conversely, insult and profanity were the typical types men uttered during the movie. In regard to the motives of using taboo words, it was discovered that psychological, social and linguistic motives tend to stimulate male characters to utter taboo words, while women are merely affected by psychological and social  motives. From the results, the research concludes that female characters utter taboo words more variably than men. However, women’s variability on the production of taboo words is limited to certain situations, while men apply taboo words in multiple contexts.